SAT0157 Tocilizumab Serum Trough Levels Correlate with Clinical Activity in Rheumatoid Arthritis. (15th July 2016) - Tornero Marín, C.; Plasencia, C.; Pascual Salcedo, D.; Jurado, T.; Paredes, M.B.; Monjo, I.; Moral, E.; Pieren, A.; Bonilla Hernán, G.; Peiteado, D.; Bogas, P.; Nuño, L.; et al.
Abstract : Background: Tocilizumab (TCZ), a humanized anti-IL-6 receptor antibody, represents a new treatment strategy for RA patients.Several studies have demonstrated the association between high serum levels of TNF-inhibitors and a good clinical response in patients with RA. Little evidence exists on this relationship for other biological therapies. Objectives: To evaluate the association between TCZ serum through levels and disease activity in a cohort of RA patients after one year of treatment with TCZ. Methods: 34 RA patients treated with Tocilizumab were included. Clinical activity was assessed using the Disease Activity Score 28 (DAS28-ESR) and the Clinical and Simplified Activity Index (CDAI and SDAI), serological improvement by C-Reactive Protein- CRP- and Erythrocyte Sedimentation Rate-ESR, clinical improvement by the delta-DAS 28 and response to treatment using EULAR criteria at baseline and after one year of treatment. We stratified all patients into quartiles according to the tocilizumab levels (μg/ml) as follows: IQR1: <3, 4, IQR2: 3, 4–11, 2, IQR3: 11, 2–18, 5 and IQR4 >18.5. A last observation carried forward analysis (LOCF) was performed at the first year of treatment, so patients that dropped out of the therapy before this period were included. Blood samples were collected just before intravenous (i.v) infusion. Serum drug levels were determined by a capture enzymelinked immunosorbent assay (ELISA). Results: The baseline demographic and clinical characteristics are shown in Table 1 . When patients were categorised into quartiles, IQR1 comprised 8 (24, 2%) patients; IQR2, 7 (21, 2%); IQR3, 8 (24, 2%) and IQR4, 10 (30, 3%). Clinical activity (DAS28, CDAI and SDAI) was statistically significant higher in patients with lower serum through levels at the first year [DAS28 (IQR1: 4, 46 ±1, 5, IQR2: 2, 58 ± 0, 87, IQR 3: 3, 6± 0, 79; IQR4: 2, 17 ± 0, 74; p=0, 001), CDAI (IQR1: 23±13, 9, IQR2: 7, 72 ± 4, 44, QIR 3: 13, 38± 4, 35, IQR4: 6, 33 ± 4, 62; p=0, 003) and SDAI (IQR1: 19, 46 ±15, 5, IQR2: 9, 51± 7, 4, IQR3: 12, 59 ± 6, 31, IQR4: 4, 55 ± 3, 73; p=0, 005)] and also was the number of swollen joints (IQR1: 7, 5 ± 6, 6, IQR2: 2, 29 ±2, 06, IQR3: 5, 63 ± 4, 3, IQR4: 1, 1 ± 1, 6, p=0, 013) and tender joints (IQR1: 5, 5 ± 5, 7, IQR2: 1, 71 ± 2, 06, IQR3: 3, 13 ± 2, 8, IQR4: 0, 8 ± 0, 9, p=0, 014). In addition, the EULAR reponse was worse in those patients with lower serum drug levels [non-responders: 4 (66, 7%) in IQR1 vs 1 (16, 7%) in IQR2 vs 1 (16, 7%) in IQ3 vs 0 (0%) in IQR4, moderate responders: 3 (37, 5%) in IQR1 vs 0 (0%) in IQR2 vs 4 (50%) in IQR3 vs 1 (12, 5%) in IQR4 and good responders: 1 (5, 3%) in IQR1 vs 6 (31, 6%) in IQR2 vs 3 (37, 5%) in IQR3 vs 9 (47, 4%) in IQR4, p=0, 006]. In terms of acute-phase reactants, the mean ESR tended to be higher in patients with lower TCZ levels (IQR1: 22, 6±14, 8 vs IQR2: 5, 6±1, 6 vs IQR 3: 9, 4 ±3, 5 vs IQR4: 6, 4 ± 3, 5, p=0, 005), and also CRP levels (RIQ1: 10, 2±17, 4 vs RIQ2: 2, 3 ± 3, 4 vs RIQ3 0, 56 ± 0, 4 vs RIQ 4: 0, 42 ± 0, 66, p=NS)]. Conclusions: The presence of low serum Tocilizumab levels correlates with a worse clinical disease activity. Consequently, measurement of Tocilizumab levels is a valuable tool that might help in the clinical management of patients with Rheumatoid Arthritis. Disclosure of Interest: C. Tornero Marín Grant/research support from: Funded by an unrestricted medical grant from Pfizer., C. Plasencia: None declared, D. Pascual Salcedo: None declared, T. Jurado: None declared, M. B. Paredes: None declared, I. Monjo: None declared, E. Moral: None declared, A. Pieren: None declared, G. Bonilla Hernán: None declared, D. Peiteado: None declared, P. Bogas: None declared, L. Nuño: None declared, A. Villalba Yllan: None declared, E. Martín Mola: None declared, A. Balsa Criado: None declared